2014
DOI: 10.1680/iasma.13.00013
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the relationship between BIM and asset management

Abstract: The purpose of this paper is to explain the mutually supportive relationship between building information modelling (BIM) and asset management. In doing so, it will enhance the ability of infrastructure owners and their suppliers to develop and implement processes, tools and collaborative working practices that optimise infrastructure asset costs and performance over the entire life cycle of assets. The paper has been produced to help mitigate the danger of treating BIM and asset management as isolated practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…AM also enables asset owners to examine the performance of their assets and related systems to achieve organizational requirements and also integrates all management systems to overwhelm operating in silos (Cooksey et al 2010). Accordingly, AM transforms business objectives into asset-related decisions and assists in financial decision-making, short-term and long-term planning, and in generating scheduled work orders (Pocock et al 2014). Appropriate and reliable assets information; such as asset location, specifications, warranties and maintenance schedules, in a well-structured form are essential for supporting effective decision making during asset operation and management stage Nicał and Wodyński 2016).…”
Section: Introductionmentioning
confidence: 99%
“…AM also enables asset owners to examine the performance of their assets and related systems to achieve organizational requirements and also integrates all management systems to overwhelm operating in silos (Cooksey et al 2010). Accordingly, AM transforms business objectives into asset-related decisions and assists in financial decision-making, short-term and long-term planning, and in generating scheduled work orders (Pocock et al 2014). Appropriate and reliable assets information; such as asset location, specifications, warranties and maintenance schedules, in a well-structured form are essential for supporting effective decision making during asset operation and management stage Nicał and Wodyński 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is sometimes accompanied by challenges regarding the interoperability of information models with all the other organisational asset information system(s). Therefore, information requirements should be set out by the facilities management early in the projects, to ensure the delivered information models are compatible (Pocock et al, 2014).…”
Section: Financial Asset Managementmentioning
confidence: 99%
“…The potential of BIM to facilitate architects and engineers in design works as well as the construction of the facilities is inarguable. It was claimed that Stage 7 (In Use) will receive the biggest impact if BIM is implemented in the property development project (Pocock et al, 2014). Pocock et al 2014 suggested how the building owner and the professionals such as engineers and architects could benefit in the implementation of BIM in their projects.…”
Section: The Integration Of Building Information Modelling (Bim) Intomentioning
confidence: 99%